Text-fig. 10. a, b: Carpinus aff. betulus. a: Leaves, Oriolo MSF 640. b: Fruit, Oriolo MSF 985. c–g: Carpinus aff. orientalis. c: Oriolo MSF 895. d: Oriolo MSF 899. e: Oriolo MSF 848. f: Fruit, Oriolo MSF 986. g: Fruit, Oriolo MSF 985. Scale bars 10 mm (a–g). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 10. a, b: Carpinus aff. betulus. a: Leaves, Oriolo MSF 640. b: Fruit, Oriolo MSF 985. c–g: Carpinus aff. orientalis. c: Oriolo MSF 895. d: Oriolo MSF 899. e: Oriolo MSF 848. f: Fruit, Oriolo MSF 986. g: Fruit, Oriolo MSF 985. Scale bars 10 mm (a–g). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 237, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867